Nilai-Nilai Sufistik Dalam Novel: Analisis Semiotika Pada Penggallah Kepalamu dan Persembahkan Pada Mursyidmu Karya Maya Safira Muchtar - Wahyudi, muhammad Yusril; Malik, Abdul; Tayib, Mukhtar (IAINU Kebumen, 2025)
Literature is the expression of thoughts, feelings, and emotions conveyed by the author, resulting in a work that contains elements of beauty. The aim of this study is to explore the Sufistic values in the novel